Answer:
16 minutes
Step-by-step explanation:
Answer: No
Step-by-step explanation:
According to triangle inequality theorem which state that: the sum of any 2 sides of a triangle must be greater than the measure of the third side.
Now let's test the given parameters if they obey this theorem
4 inches, 5 inches and 1 inch
4 + 5 = 9
9 > 1 correct
5 + 1 = 6
6 > 4 correct
4 + 1 = 5
5 not > 5 wrong
Therefore he won't be able to create the triangular component with these toothpicks without modifying any of the lengths
Answer:
C. Tiffany, born in 1973 in Nebraska, has lived in the U.S. for 45 years
Step-by-step explanation:
its right bro
Answer:
B it right...
Step-by-step explanation:
Answer: -7twice
Step-by-step explanation:
This is a question on root of quadratic equation. The interpretation of the question
x² 14x + 49 is
x² + 14x + 49 = 0.meaning that we are to find two possible values for x that will make the expression equal 0.
We can use any of the methods earlier taught. For the purpose of this class, I am using factorization methods
x² + 14x + 49 = 0
Now, find the product of the first and the last terms, is
x² × 49 = 49ײ
Now find two terms such that their productbis 49x² and their sum equals 14x, the one in the middle.
We have several factors of 49x² but only one will give sum of 14x. Because of the time, I will only go straight to the required factors .
49x² = 7x × 7x and the sum gives 14x the middle terms..
Now we now replace the middle one by the factors and then factorize by grouping.
x² + 14x + 49 = 0
x² + 7x + 7x + 49 = 0
x(x + 7) + 7(x + 7) = 0
(x + 7)(x + 7). = 0
Now to find this value of x,
x + 7 = 0
x. = -7twice.
The root of the equation = -7twice.